Analisis Perkembangan Tingkat Utang, Ukuran Perusahaan, dan Arus Kas Operasi Pada Sektor Properti dan Real Estate Selama 5 Tahun Terakhir - Pujiastuti Pangestu, Rizma; Pahala, Indra; Handarini, Dwi (Jurnal Akuntansi, Perpajakan dan Auditing, 2025)
This study aims to analyze the development of debt levels, company size, and operating cash flow in the property and real estate sector over the last 5 years. The method used in this research is descriptive statistical analysis using secondary data from the financial statements of 55 property and real estate companies listed on the IDX during the period 2019-2023. The analysis technique used is the DER as a proxy for debt levels, total assets as a proxy for company size, and the operating cash flow ratio. The results of the study indicate that the debt levels of the sample are still below the industry average, but there is an increase in total assets as a proxy for company size. Meanwhile, the average operating cash flow ratio for companies in this sector is below 1.